Modeling and Fuzzy Logic Control of PV Based Cascaded Boost Converter Three Phase Five-level Inverter System - Guruswamy Revana; Venkata Reddy Kota (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Power Quality development using PV based boost cascaded inverter system is one of the reliable methods. This paper handle with modeling and fuzzy logic control of boost to boost cascaded three phase inverter system with PV as source. MATLAB simulink model for BBCIS has been developed using the elements of simulink and cascaded loop investigations are performed with PI and Fuzzy Logic Controllers. The dynamic responses of the above systems are compared in terms of time domain parameters. The consequences point to that maximum power is obtained with minimum THD using FLC.